2016
DOI: 10.1080/15376516.2016.1196281
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses following active and passive smoking of tobacco and electronic cigarettes

Abstract: Context: It has been indicated that acute active and passive tobacco cigarette smoking may cause 22 changes on redox status balance that may result in significant pathologies. However, no study has 23 evaluated the effects of active and passive e-cigarette smoking on redox status of consumers. 24Objective: To examine the acute effects of active and passive e-cigarette and tobacco cigarette smoking 25 on selected redox status markers. 26Methods: Using a randomized single-blind crossover design, 30 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…The participants were asked not to smoke before having blood drawn, but studies have indicated that tobacco and e-cigarette smoking exposure does not acutely alter the response of the antioxidant system, neither under active nor passive smoking conditions. It was demonstrated that total antioxidant capacity, catalase activity (CAT) and reduced glutathione (GSH) remained similar to baseline levels immediately after and 1 h-post exposure of persons who smoked two cigarettes within 30 min and a group of active e-cigarette smoking persons who smoked a pre-determined number of puffs in the same time, using a liquid containing 11 ng/mL nicotine [48].…”
Section: Discussionmentioning
confidence: 99%
“…The participants were asked not to smoke before having blood drawn, but studies have indicated that tobacco and e-cigarette smoking exposure does not acutely alter the response of the antioxidant system, neither under active nor passive smoking conditions. It was demonstrated that total antioxidant capacity, catalase activity (CAT) and reduced glutathione (GSH) remained similar to baseline levels immediately after and 1 h-post exposure of persons who smoked two cigarettes within 30 min and a group of active e-cigarette smoking persons who smoked a pre-determined number of puffs in the same time, using a liquid containing 11 ng/mL nicotine [48].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C plays an important role in the defense of the first antioxidants against oxidant agents in plasma. It is an important antioxidant that reacts with superoxide and hydroxyl radicals and cleans them, and it makes tocopherol radicals turn into tocopherol again . In the study carried out by Tug et al in patients with COPD, it was determined that vitamins A and E levels decreased during the attack and vitamin C level did not change.…”
Section: Discussionmentioning
confidence: 99%
“…The airborne nicotine concentrations emitted by various brands of e-cigarettes ranged from 0.82 to 6.23 μg/m 3 [63]. In non-users who are exposed to secondhand aerosols from e-cigarettes, common respiratory endpoints can include an increase in asthma symptoms and severity, and a higher prevalence of upper and lower respiratory tract symptoms and infections [64,65]. Due to observed changes in indoor air quality, it has been recommended restricting the use of e-cigarettes in all indoor public areas [66].…”
Section: Secondhand Vaping and Respiratory Health – What Do We Know Smentioning
confidence: 99%